2011
DOI: 10.1007/s00203-011-0680-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of a thermoregulated type VI secretion system by AHL-dependent Quorum Sensing in Yersinia pseudotuberculosis

Abstract: The type VI secretion system (T6SS) is a novel secretion system found in many Gram-negative bacterial pathogens, which appears to be tightly regulated by different regulatory mechanisms. In the present study, we identified 4 T6SS clusters in Yersinia pseudotuberculosis and demonstrated that they were differentially thermoregulated. Among them, T6SS4 was preferentially expressed at 26°C, and its expression was growth phase dependent and subject to quorum sensing regulation. Both YpsI and YtbI AHL synthases cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 47 publications
4
54
0
1
Order By: Relevance
“…Previous reports indicated that the expression of T6SS genes is growth phase-dependent in V. cholera, Y. pestis, and Y. pseudotuberculosis (Ishikawa et al 2009;Pieper et al 2009;Zhang et al 2011). Similarly, we observed that there was higher expression level of the T6SS hcp1 gene at exponential phase versus stationary phase (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Previous reports indicated that the expression of T6SS genes is growth phase-dependent in V. cholera, Y. pestis, and Y. pseudotuberculosis (Ishikawa et al 2009;Pieper et al 2009;Zhang et al 2011). Similarly, we observed that there was higher expression level of the T6SS hcp1 gene at exponential phase versus stationary phase (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, we observed that 11 out of 18 genes in a homologous T6SS-4 cluster in the IP32953 strain were upregulated in the ⌬tatC mutant background at 26°C in stationary phase (see Table S2 in the supplemental material). Previous reports have shown the T6SS-4 cluster to be highly expressed at 26°C during stationary phase but downregulated at 37°C (30). The T6SS-4 cluster is important for Y. pseudotuberculosis survival under acidic conditions, high osmolarity, and exposure to the detergents, such as deoxycholate, that impair outer membrane integrity.…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, a highly conserved DUF2285 homolog is encoded adjacent to the QS (39) and temperature-dependent (40) type VI secretion system (T6SS-4) present in Yersinia species. Although the protein-coding capacity of this region has not been investigated, the region has been directly implicated in the regulation of T6SS-4 expression (39,41,42).…”
Section: Discussionmentioning
confidence: 99%